Analisa Keputusan Jalur Distribusi Produk Deterjen Melalui Distribution Center Dengan Metode Vogel Pada Minimarket di Serang - Hosianna, Glory Riama; Ningsih, Tri Wahyu (Universitas Mercu Buana, 2020)
Along with the development of the areas around the city of Serang caused the growth of modern retail locations (minimarkets) on the outskirts of the city of Serang. This research observes the development of minimarkets in small cities in the area of Serang based on their specific function, namely as a labor-intensive industrial area (Cikande). Distribute the products to customer use logistical distribution channels to meet the demands of each retail location. Distribution is a path that must be traversed by the flow of goods from producers to agents or intermediaries or wholesalers to users, in this case consumers. Distribution are very important in company activities, because this will affect the decisions made by company managers. The purpose of this study is to analyze the product distribution path from the Distribution Center to the Retail location by using the Vogel method where Vogel‟s Approximation Method (VAM) is one method that is often used to find the minimum cost for transportation problems. The result of this case is use 2 Distribution Centers for minimum cost.Along with the development of the areas around the city of Serang caused the growth of modern retail locations (minimarkets) on the outskirts of the city of Serang. This research observes the development of minimarkets in small cities in the area of Serang based on their specific function, namely as a labor-intensive industrial area (Cikande). Distribute the products to customer use logistical distribution channels to meet the demands of each retail location. Distribution is a path that must be traversed by the flow of goods from producers to agents or intermediaries or wholesalers to users, in this case consumers. Distribution are very important in company activities, because this will affect the decisions made by company managers. The purpose of this study is to analyze the product distribution path from the Distribution Center to the Retail location by using the Vogel method where Vogel‟s Approximation Method (VAM) is one method that is often used to find the minimum cost for transportation problems. The result of this case is use 2 Distribution Centers for minimum cost.